Morphotectonic Indicators of Wadi Al-Manai Basin in the Western Plateau of Iraq (Iraqi National Journal of Earth Science (INJES), 2026)
The Al-Man'i Basin is one of the seasonal valleys located at the end of the Euphrates River, in the northern part of the western Iraqi plateau, within the lower valleys region. Its basin area is 3634 km2. The Al-Man'i Basin and its minor basins were studied to demonstrate the degree of tectonic activity and its impact on the form of the basin. This was conducted after studying the structural features of the area, which revealed the existence of five subsurface faults, five subsurface anticlines, and the presence of 85 linear structures. These structures have influenced the morphometric characteristics of the basins. The calculated geomorphological indicators were also demonstrated through the analysis of the digital elevation model (DEM) using geographic information systems (GIS). The tectonic situation in this area was evaluated through gathering geomorphological indicators, including the topographic symmetry index (T), the asymmetry index (AF), the stream length and slope index (SL), the valley width to height ratio index (VF), and the basin shape index (BS). After analyzing the indicators for each basin and comparing them with the final classification grades (IRAT), it was found that the main basin exhibits low tectonic activity. In contrast, the secondary basins vary in activity levels: the basins of Al-Manea Al-Sharqi, Batikha, and Al-Jabriya show low tectonic activity and cover a total area of 1408 km2. Meanwhile, the basins of Al-Dayea, Al-Maani, Darb Al-Saai, and Ja’ata demonstrate medium tectonic activity, encompassing a total area of 2226 km2. Overall, this indicates a lack of significant tectonic activity in the region, which aligns with the geological characteristics of the area, situated within the stable platform of Iraq.
Keywords: Topographic symmetry, Asymmetry, Tectonic activation, Topographic asymmetry.